Herramientas ofimáticas en educación virtual en tiempos de pandemia. - Aldaz, Ángel M. (2022)
ABSTRACT The purpose of this article is to identify the causes presented by students in the absence of the subject of Computer Science Applied to Education in virtual education in time of pandemic. The mastery of office tools and digital platforms are the problem that was detected in First-year Unified General Baccalaureate students, affecting their academic development. For which the methodology used is documentary that allows expanding the worldview of the causes and effects of the problem, supported by field research for the collection of information, the SPSS software was used for statistical analysis and hypothesis testing. Regarding the results obtained, the students report that during the virtual education they were disoriented since they did not know the proper functioning of office tools as well as virtual environments. In the survey of 115 students, the hypothesis testing test was applied, obtaining a considerable positive correlation with a margin of error of less than 5%, accepting the alternative hypothesis and rejecting the null hypothesis. Concluding that there is a relational trend between the mastery of office tools and the absence of the subject of Computer Science Applied to education.